The effect of chronoradiotherapy on cervical cancer patients: A multicenter randomized controlled study - Wang, Ying; Qiang, Wan-Min; Li, Jia-Qian; Shen, Ao-Mei; Chen, Xiao-Cen; Li, Xiao-Fang; Zhang, Bao-Zhong; Xie, Juan; Yan, Rong; Li, Xiang-Hua; Zhang, Zhao-Li; Wang, Cui-Ling; et al. (Frontiers in Oncology, 2022)
Objectives To investigate the short-term efficacy and radiotoxicity of chronoradiotherapy in patients with cervical cancer. We also examined the overall symptom score and quality of life (QOL) of patients who underwent morning radiotherapy and evening radiotherapy. Methods We conducted a multicenter randomized controlled trial to compare the effects of morning radiotherapy (9:00–11:00 AM) with evening radiotherapy (7:00–9:00 PM) in cervical cancer patients receiving radiotherapy. From November 2021 to June 2022, 114 cervical cancer patients admitted to eight cancer center hospitals in Tianjin, Chongqing, Hubei, Shanxi, Shandong, Shaanxi, Hebei, and Cangzhou were randomly divided into the morning radiotherapy group (MG; N = 61) and the evening radiotherapy group (EG; N = 53). The short-term efficacy of radiotherapy on cervical cancer patients at different time points and the occurrence of radiotoxicity were explored after patients had undergone radiotherapy. Results The total effective response (partial remission [PR] + complete remission [CR]) rate was similar across the two groups (93.5% vs. 96.3%, p > 0.05). However, the incidence of bone marrow suppression and intestinal reaction in the two groups were significantly different (p < 0.05). The patients in the MG had significantly higher Anderson symptom scores than patients in the EG (21.64 ± 7.916 vs. 18.53 ± 4.098, p < 0.05). In terms of physical activity, functional status, and overall QOL, the MG had significantly lower scores than the EG (p < 0.05). No other measures showed a significant difference between the groups. Conclusion The radiotherapy effect in the MG is consistent with that of EG. The incidence of radiation enteritis and radiation diarrhea in the MG was significantly higher than that in the EG; however, bone marrow suppression and blood toxicity in the EG were more serious than in the MG. Because of the small sample size of the study, we only examined the short-term efficacy of radiotherapy. Therefore, further clinical trials are needed to verify the efficacy and side effects of chronoradiotherapy.